Fatal Case of Chromobacterium violaceum Bacteraemia - Muharam, Nur Hafiza; Hussin, Azura; Deris, Zakuan Zainy (Bangladesh Journal of Medical Science, 2019)
Chromobacterium violaceum is rarely associated with human infection in tropical and subtropical regions. We report a fulminant fatal case of bacteremia in a 52-year-old lady, with underlying diabetes mellitus, who was presented with a month history of back swelling associated with fever, lethargy and poor oral intake. C. violaceum was isolated from blood and identify by standard biochemical test.However the patient’s condition deteriorating rapidly and succumbed to death on the day of admission. In these regions, C. violaceum should be one of the differential causes of sepsis, especially if the patient presented with skin lesions and/or multiple organ abscesses with history of exposure to soil or stagnant water. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.434-436